A 5-hydroxytryptophan-secreting carcinoid tumour. Issue 1 (March 1963) - Campbell, A. C. P.; Gowenlock, A. H.; Platt, D. S.; Snow, P. J. D.
Abstract : An atypical case of the malignant carcinoid syndrome, associated with multiple peptic ulcers, is described. The tumour cells were argyrophil but not argentaffin, and the tumour was found to contain 5-hydroxytryptophan (5-H.T.P.) but not 5-hydroxytryptamine (5-H.T.). This aberrant biochemical behaviour was associated with the virtual absence of 5-H.T.P.-decarboxylase from the tumour tissue. The tumour contained notable quantities of histamine.